Tissue-Specific Transcriptomic Profiling of Sorghum propinquum using a Rice Genome Array - Zhang, Ting (Public Library of Science, 2013)
Sorghum (Sorghum bicolor) is one of the world's most important cereal crops. S. propinquum is a perennial wild relative of S. bicolor with well-developed rhizomes. Functional genomics analysis of S. propinquum, especially with respect to molecular mechanisms related to rhizome growth and development, can contribute to the development of more sustainable grain, forage, and bioenergy cropping systems. In this study, we used a whole rice genome oligonucleotide microarray to obtain tissue-specific gene expression profiles of S. propinquum with special emphasis on rhizome development. A total of 548 tissue-enriched genes were detected, including 31 and 114 unique genes that were expressed predominantly in the rhizome tips (RT) and internodes (RI), respectively. Further GO analysis indicated that the functions of these tissue-enriched genes corresponded to their characteristic biological processes. A few distinct cis-elements, including ABA-responsive RY repeat CATGCA, sugar-repressive TTATCC, and GA-responsive TAACAA, were found to be prevalent in RT-enriched genes, implying an important role in rhizome growth and development. Comprehensive comparative analysis of these rhizome-enriched genes and rhizome-specific genes previously identified in Oryza longistaminata and S. propinquum indicated that phytohormones, including ABA, GA, and SA, are key regulators of gene expression during rhizome development. Co-localization of rhizome-enriched genes with rhizome-related QTLs in rice and sorghum generated functional candidates for future cloning of genes associated with rhizome growth and development.